The postural effect of different types of load carriage in ergonomic during walking gait - Ng, Xiao Jing (2023)
This study investigates the impact of different backpack types and varying loads on the postural dynamics of young female adults during walking gait. The objectives were to analyze spatiotemporal, kinematic, and kinetic parameters in traditional and ergonomic backpacks with different loads and to compare their effects on posture. Data were collected from twenty female subjects (22 ± 1 years, 161 ± 6 cm, and 52 ± 6 kg), and analyses were conducted on parameters including cadence, step length, stride length, trunk flexion angle, ankle and knee range of motion (RoM), pelvic RoM (tilt, obliquity, rotation), as well as vertical ground reaction forces (VGRF). The results revealed that load variations did not significantly affect lower limb parameters, while heavier loads did impact VGRF, trunk flexion angle, and pelvic obliquity RoM (p < 0.05). Notably, there was no significant difference in VGRF between ergonomic and traditional backpacks, challenging marketing claims of substantial weight reductions. However, ergonomic backpacks did reduce trunk flexion angle (p < 0.05). These findings emphasize the importance of selecting backpacks that prioritize comfort and proper weight distribution to mitigate musculoskeletal stress and injury risk during daily activities.